Dissemination of NDM-1 in pseudomonas aeruginosa and klebsiellapneumoniae isolated from pus samples in tertiary care hospitals of Quetta, Pakistan - Mohammad Din; Khan Muhammad Babar; Dawood Shah; Ghulam Sarwar; Saleem Khan; Hummaira Sadaf; Shahjahan Shabbir Ahmed; Faiza Liaqat Ali; Muhammad Yasir; Nazeer Ahmed (Journal of the Pakistan Medical Association, 2020)
Objective: To highlight the prevalence and epidemiology of New Delhi metallo-ß-lactamase-1.producers in pus samples. Methods: The cross-sectional study was conducted from April to August 2018at the Biotechnology Laboratory, Balochistan University of Information Technology Engineering and Management Sciences, Quetta, Hi-tech Laboratory, Centre for Advance Studies in Vaccinology and Biotechnology, University of Balochistan, Quetta, and Microbiology Laboratory, Bolan Medical Complex Hospital, Quetta, Pakistan. Biochemical and molecular approaches were used for the identification of the isolates and Modified Hodge Test for the phenotypic detection of class-A carbapenemase activity. Minimum Inhibitory Concentration was performed using E-test and broth microdilution method. Molecular basis of carbapenemase activity was ascertained by the recognition of blaNDM-1 gene in the isolates. Results: Of the 300 pus samples taken from surgical/burn units,6(2%) blaNDM-1 harbouring isolates were found; 3(50%) each being Klebsiellapneumoniae andPseudomonas aeruginosa. Klebsiella. pneumoniaeisolates were extensivelydrug-resistant. The Pseudomonas aeruginosaisolates displayed resistance against 21 antibiotics of tetracyclines, quinolones, ?-lactams, aminoglycosides, monobactams, sulphonamides, macrolides, cephalosporins, phosphonic acid and polypeptide groups, suggesting pan-drug resistance. Conclusion: The resistance pattern of the bacterial isolates poses a significant clinical threat in the region. Key Words: blaNDM-1, Carbapenemase, XDR, PDR, Quetta. Continuous...